A 21-Year-Old Woman with Suspecting Gitelman Syndrome - Denny, Berty; Agung Prabowo, Nurhasan; Puspa Putri, Desy; Myrtha, Risalina; Apriningsih, Hendrastutik (Faculty of Medicine Universitas Sebelas Maret, 2022)
Introduction: Gitelman syndrome (GS), is a hereditary condition marked by a specific kidney function impairment. GS symptoms do not normally manifest until beyond the age of six years. We present a rare case of a 21-year-old woman with a background in generalized weakness muscle cramps with tetany, fever, and dyspnea. The goal of this study is to give a case report of Gitelman syndrome suspicion.Result: Gitelman syndrome is identified through clinical indicators and lab testing, such as low potassium and magnesium levels in the blood, metabolic alkalosis, and low calcium levels in the urine. We do a variety of physical and laboratory tests to determine the disease and rule out other possibilities. Molecular proof is difficult to get due to a lack of resources and the high expense of genetic testing, which has become one of our case report's flaws. This patient was diagnosed as suspecting Gitelman syndrome and treated for electrolyte imbalances. The patients were given replacement therapy, which comprised intravenous potassium, sodium, and chloride therapy, as well as calcium therapy. In addition, we also provided some symptomatic therapy. She was discharged five days later in fine condition.Conclusion : This is one of the few reports of a 21-year-old lady being suspected of having Gitelman syndrome (GS). We conduct a battery of physical and laboratory tests to diagnose the disease and rule out other possibilities. We provide the appropriate therapies in accordance with the guidelines, and the outcomes are favorable.